Mutation in noncoding RNA RNU12 causes early onset cerebellar ataxia. Issue 1 (24th January 2017) - Elsaid, Mahmoud Fawzi; Chalhoub, Nader; Ben‐Omran, Tawfeg; Kumar, Pankaj; Kamel, Hussein; Ibrahim, Khalid; Mohamoud, Yasmin; Al‐Dous, Eman; Al‐Azwani, Iman; Malek, Joel A.; Suhre, Karsten; Ross, M. Elizabeth; et al.
Abstract : Objective: Exome sequences account for only 2% of the genome and may overlook mutations causing disease. To obtain a more complete view, whole genome sequencing (WGS) was analyzed in a large consanguineous family in which members displayed autosomal recessively inherited cerebellar ataxia manifesting before 2 years of age. Methods: WGS from blood‐derived genomic DNA was used for homozygosity mapping and a rare variant search. RNA from isolated blood leukocytes was used for quantitative polymerase chain reaction (PCR), RNA sequencing, and comparison of the transcriptomes of affected and unaffected family members. Results: WGS revealed a point mutation in noncoding RNA RNU12 that was associated with early onset cerebellar ataxia. The U12‐dependent minor spliceosome edits 879 known transcripts. Reverse transcriptase PCR demonstrated minor intron retention in all of 9 randomly selected RNAs from this group, and RNAseq showed splicing disruption specific to all U12‐type introns detected in blood monocytes from affected individuals. Moreover, 144 minor intron–containing RNAs were differentially expressed, including transcripts for 3 genes previously associated with cerebellar neurodegeneration. Interpretation: Interference with particular spliceosome components, including small nuclear RNAs, cause reproducible uniquely distributed phenotypic and transcript‐specific effects, making this an important category of disease‐associated mutation. Our approach to differential expression analysis of minor intron–containing genes is applicable to other diseases involving altered transcriptome processing. ANN NEUROL 2017;81:68–78